The history of Camp Tophat : the story of an American city that grew on the banks of the Schelde and of the personalities that made it grow - Rand, John B. (S.l. : s.n., 1946)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; Naoorlogstijd; Antwerpen